Evaluating a sustainability index for nutrients in a short rotation energy cropping system - Sochacki, S.; Harper, R.; Smettem, K.; Dell, B.; Wu, Hongwei (Wiley-Blackwell, 2013)
In dryland environments 3–5 year rotations of tree crops and agriculture represent a major potential bioenergy feedstock and a means to restore landscape hydrologic balances and phytoremediate sites, while maintaining food production. In soils with low natural fertility, the long-term viability of these systems will be critically affected by site nutrient status and subsequent cycling of nutrients. A nutrient assimilation index (NAI) was developed to allow comparison of species and tree component nutrient assimilation and to optimize nutrient management, by quantifying different strategies to manage site nutrients. Biomass, nutrient export and nutrient use efficiency were assessed for three short rotation tree crop species. Nutrient exports following harvest at 3 years of high density (4000 trees ha-1) were consistently higher in Pinus radiata, with values of 85 kg ha-1 of N, 11kg ha-1 of P, and 62 kg ha-1 of K, than Eucalyptus globulus and Eucalyptus occidentalis. Component NAI was generally in the order of leaf < twig < bark < root < stem-wood for N, P, K, S, Ca, and Mg. The NAI ranged from 0.06 Mg kg-1 for N in leaves of P. radiata to 4.7 Mg kg-1 for P in stem-wood of E. occidentalis, indicating highersustainability of wood biomass compared with leaf biomass. The leaves for each species contained between 40 and 60% of the total nutrient contents while comprising around 25–30% of the total biomass. These nutrient exports via biomass removal are similar to those that follow 3 years of wheat production in the same region, indicating there is no additional drawdown of nutrient reserves during the tree cropping phase of the rotation.